Проблеми і перспективи селекційно-генетичного вдосконалення яблуні (Malus Mill.) - Опалко, А.І.; Опалко, О.А. (Фактори експериментальної еволюції організмів, 2015)
Aims. The prevalence of an apple trees in the fruit plantations of Ukraine as well as in the other parts of the world with temperate climate is explained by unusual combination of high fl avouring and dietary quality of its fruits with great index, transportability and long-term preservation capacity. In spite of the essential increase of apple production in Ukraine the absolute data of Poland twice as much of that in Ukraine, nevertheless its agro-ecological conditions are less suitable for apple growing. Methods. The method of group sample for the retrospective review of the experimental and theoretical researches which have been done all over the different countries of the world was used in order to clarify the urgent matters so as to select and improve the breeding and genetics prospects of an apple. Results. The apple cultivars which have been growing in farming as scion/rootstock combination are combine the targets of breeding apple scion (cultivar where the fruits are formed) so as the rootstock improvement which was the basis of root nutrition in the fruit tree. Anthropoadaptive features complex of the newly-created cultivars has more than 50 important indices hereby the list and economic sense of them should be changed essentially depending from the district, population prosperity and feeding culture dynamics. Conclusions. Rise in the apple production of Ukraine in order to replenish the home market with the prospect to come out to the world market wholly depend from the breeding and genetics support of the sector of fruit production. The breeders and geneticists forces should be referred in the direction of apple anthropoadaptability complex improvement as the as the top fruit in Ukraine. Keywords: anthropoadaptability, cultivar, scion, stock apple, self-incompatibility alleles.